2019
DOI: 10.1016/j.cbi.2018.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Increasing complexity and interactions of oxidative stress in chronic respiratory diseases: An emerging need for novel drug delivery systems

Abstract: Increasing complexity and interactions of oxidative stress in chronic respiratory diseases: An emerging need for novel drug delivery systems, Chemico-Biological Interactions (2019), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 109 publications
(57 citation statements)
references
References 99 publications
0
57
0
Order By: Relevance
“…Respiratory diseases like lung cancer, inflammatory diseases with chronic obstructive pulmonary disease (COPD), asthma, respiratory infections and pulmonary fibrosis are some of the major causes of death globally [1][2][3]. Currently available treatment options for these diseases have limited efficacy [4].…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory diseases like lung cancer, inflammatory diseases with chronic obstructive pulmonary disease (COPD), asthma, respiratory infections and pulmonary fibrosis are some of the major causes of death globally [1][2][3]. Currently available treatment options for these diseases have limited efficacy [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we also explored the association of lncRNA NEAT1 expression with disease condition as well as inflammation level in patients with AIS, and we observed that lncRNA NEAT1 high expression was associated with increased NIHSS score, raised CRP level, elevated pro‐inflammatory cytokines levels (including TNF‐α, IL‐6, IL‐8, and IL‐22), and reduced anti‐inflammatory cytokine level (IL‐10) in patients with AIS. The possible reasons for these results might be as follows: (a) lncRNA NEAT1 might enhance the dysfunction of cerebral microglial cells through Wnt/β‐catenin signaling pathway, thus, it contributed to impairing the normal cerebrovascular physiology that led to advanced disease severity, and consequently, elevated NIHSS score was found in lncRNA NEAT1 high expression patients with AIS; (b) lncRNA NEAT1 might induce the loss of motor neurons and lead to the devastating neurodegenerative disorder, thus aggravated the abnormal cognitive deficits and functional activities of patients with AIS and increased the NIHSS score; (c) lncRNA NEAT1 promoted intima thickening or vascular occlusion by modulating the phenotype conversion of vascular smooth muscle cells, together with excessive apoptosis of epithelial cells, which might enhance the atherosclerotic lesion and aggravate the severity of AIS, thus lncRNA NEAT1 correlated with increased NIHSS score; (d) lncRNA NEAT1 might enhance the reactive oxygen species (ROS) level to disturb the normal initiation of inflammatory cascades, which further induced excess production of inflammatory cytokines, and thus, it led to increased levels of inflammatory factors (including CRP, TNF‐α, IL‐6, IL‐8, and IL‐22) as well as reduced anti‐inflammatory cytokine level in patients with AIS …”
Section: Discussionmentioning
confidence: 99%
“…The Gα subunit binds to either GTP or GDP; Gβ and Gγ subunits form a constitutive heterodimer that binds reversibly to the Gα subunit. GTP binding activates the Gα subunit, and the resulting conformational changes lead to dissociation from the receptor and from Gβγ subunits (Dua et al, ; Gupta et al, ). These free subunits are now competent to interact with the downstream enzymes or channels to drive second messenger generation or changes in membrane potential that modulate cell physiology (Campbell & Smrcka, ).…”
Section: Involvement Of G‐protein‐coupled Receptor Kinase (Grk) Signamentioning
confidence: 99%